ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH (PAD) di KOTA MALANG (Studi Kasus di Badan Pelayanan Pajak Daerah (BP2D) Kota Malang) - Reka Wijayanti; Noor Shodiq Askandar; Mohammad Amin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research aims to determine the level of effectiveness and contribution ofadvertisement tax to Local Original Income in Malang city. The method of analysisused in conducting research is by using the method of effectiveness analysis andcontribution analysis. Analysis of effectiveness using data realization of local taxrevenues and local tax revenue targets, while the contribution analysis using data theamount of realization of local taxes with the amount of realization of Local Revenue.The data collected in the form of target number and realization of local tax revenue andLocal Revenue. The results of research that has been done show that advertisement taxacceptance every year in Malang city in 2012 until year 2016 can be categorized veryeffective. The contribution of advertisement tax every year in Malang City iscategorized very less to the original regional income in 2012 until 2016.Keyword: Effectiveness, Contributions, Advertisement Tax, Local Original Income